Legal Procedure in the Monuments of Traditional Mongolian Law, 16th –18th Centuries: An Attempted Comparative Legal Analysis - Roman Yu. Pochekaev (Монголоведение, 2021)
Introduction. Mongolian codifications of 16th–18th centuries are considered to be sources of customary law. But their structure and content prove the opposite as they were results of law-making by rulers and contained different rules on status and credentials of authorities. One of such fields was legal procedure which becomes an object for analysis in this article. Goals and Objectives. The goal of our research is analysis of procedural institutions in Mongolian codifications and their evolutions from the 16th to the 18th century. To achieve this goal, one should analyze procedural rules in these codifications, find their common and specific features, correlate the content of codifications with political situation in Mongolia and, at last, trace the evolution of procedural institutions. Materials and Research Methods. The sources for research are late medieval Mongolian legal codifications: the Code of Altan Khan, ruler of Tumet in Southern Mongolia (c. 1588), Eighteen Steppe Laws established at conferences of Khalkha rulers between the 1580s and 1620s, ‘Ik Tsaaz’ (‘The Great Code’) issued at the Congress of Oirat and Mongol princes in 1640 with additional edicts of the Zunghar ruler Galdan Boshugtu Khan in the 1670s and, finally, ‘Khalkha Jirum’ (‘The Code of Khalkha’) issued from 1709 to 1770 by conferences of rulers of the Northern Mongolia. To study this documents a number of research methods were used, namely: source study, structure functional analysis, comparative historical research, formal legal approach, historical legal method and comparative legal analysis. Results. The legal procedure developed irregularly during the examined period. The status and credentials of authorities in the field of justice were substantially changed from the 16th throughout the 18th century, and that was connected with political processes in Mongolia. In particular, with centralization of power in the Zunghar Khanate in the 17th century and adaptation of Khalkha rulers to new political realities under the suzerainty of the Qing Empire since the end of the same century. As for other procedural institutions, such as evidences and their search, those remained, in fact, unchanged. That could be explained by that the procedural institutions were closer connected with customary law, and Mongolian rulers did not pay attention to their adaptation to the current situation. Discussion. However, the article is no more than a problem setting, and advanced research should include sources which still are not introduced into the scientific circulation: Code of the League of Kuku-Nor (late 17th century), court practice cases in the ‘Ulaan Hatsart’ (‘Red Notebook’, 19th – early 20th centuries). Besides that, another kinds of sources should be kept in mind, e. g., Manchurian law for Mongols (‘Tsaajin Bichig’ of the 17th century and ‘Lifanyuan Tse-li’ – Code of the Qing Ministry of Foreign Affairs, late 18th – early 19th centuries), Kalmyk legislation of the 18th century, Buryat law of 18th–19th centuries. These sources could help understand which procedural institution in the law of Mongolic peoples were kept unchanged and which ones were results of reception from the Russian or Chinese law.